The Influence of Service Quality and Consumer Trust on Purchase Decisions With Purchase Interest (Study of TransVision Customers in the East Jakarta Area) - Umar Santoso; Sylvia Sari Rosalina; Nurminingsih (LPPM Universitas Respati Indonesia, 2024)
Along with the rapid development of technology, the needs of the Indonesian people for technology-based entertainment are increasingly high. As with other countries, Indonesia has used one of the technology products in the television industry, namely Pay TV (pay TV) which offers a choice of programs (pay per view content), either via satellite or cable in its distribution to customers. The object of research is service quality and consumer confidence in purchasing decisions with buying interest, namely TransVision customers in East Jakarta. The study population was 7,150 customers. Samples were taken with the Slovin formula so that the results of rounding up 99 sample respondents were obtained. Valid respondent questionnaire 97 respondent questionnaire. he results of the study (H1) The quality of service has a significant positive effect on purchasing decisions, (H2) Consumer confidence has a significant positive effect on purchasing decisions, (H3) The quality of service has a significant positive effect on buying interest, H4) Consumer trust has a significant positive effect on buying interest, (H5) Purchasing interest has a significant positive effect on purchasing decisions, (H6) Buying interest has a significant positive effect on purchasing decisions, (H7) Consumer trust has no significant positive effect on purchasing decisions through buying interest Key words: service quality, consumer trust, buying interest